"...Depois, querida, ganharemos o mundo": reflexões sobre gênero, sexualidade e políticas públicas para travestis adolescentes, meninos femininos e outras variações - Silva, Larissa Maués Pelúcio [UNESP]; Duque, Tiago (My University, 2013)
This article originated in a research that was meant to map out and examine the life conditions of “travesti” (transgender) teenagers and youth living in the city of Campinas, state of São Paulo. We contacted our informants outside the environments usually identifi ed as the common spaces where members of this group spend their time and share their experiences, as a strategy that we believed could enable us to better perceive how they construct their subjectivities. As we began our ethnographic endeavors, we were surprised by the multiplicity of ways in which these young people experimented with gender and sexuality, yet which were, at the same time, accompanied by eff orts to fi t these experiments within available identity categories. Feminine boys, cross dressers and drags thus constructed their own ways of living the feminine, and in doing so, stirred our imagination regarding contemporary experiences and political struggles in the realm of sexuality.

A pesquisa que deu origem a este artigo pretendeu mapear e problematizar as condições de vida de travestis adolescentes e jovens que vivem na cidade de Campinas (SP). Buscamos contatá-las fora dos ambientes que têm sido identifi cados como espaços clássicos de aprendizado e sociabilidade deste segmento, acreditando que assim as mudanças e permanências nas formas de constituição dessas subjetividades poderiam se evidenciar. Ao iniciarmos nossas incursões etnográfi cas fomos surpreendidos por múltiplas experimentações de gênero e vivências de sexualidade, acompanhadas do esforço de seus protagonistas em classifi cá-las a partir das categorias identitárias disponíveis. Então, meninos femininos, “montadas” e “drags” passaram a nos mostrar outras experiências de vida no feminino, provocando nossa imaginação sobre as experiências e lutas políticas contemporâneas no campo das sexualidades.
Keywords: Feminine boys; Transgender teenagers; The limits of identity; Gender; Sexuality; Meninos femininos; Travestis adolescentes; Limites identitários; Gênero; Sexualidade